The accumulation of aluminum in the aboveground parts of green manure plants belonging to the Brassicaceae family - Gaponenko, A. M.; Gnatiuk, A. M.; Salnikova, A. V.; Rahmetov, D. B. (Plant varieties studying and protection, 2024)
Purpose. To determine the level of aluminum (Al) accumulation in plants of the Brassicaceae family, which are used in agriculture as green manure and are promising plants for soil phytoremediation. The following crops were the subject of the study: oilseed radish, variety ‘Kyianochka’ (Raphanus sativus L. var oleiformis Pars. ‘Kyianochka’), white mustard, variety ‘Soniachna’ (Sinapis alba L. ‘Soniachna’), winter rapeseed, variety ‘Horlytsia’ (Brassica napus L. ‘Horlytsia’), Sarepta mustard, variety ‘Zolotava’ (Brassica juncea (L.) Czern. ‘Zolotava’), winter turnip rape, variety ‘Oriana’ (Brassica campestris var. oleifera f. biennis D.C. ‘Oriana’), tyfon, variety ‘Fitopal’ (Brassica campestris var. oleifera f. biennis DC. ´ Brassica rapa L. ‘Fitopal’). Methods. The research was carried out in the M. M. Gryshko National Botanical Garden of the National Academy of Sciences of Ukraine (Kyiv). Plants grown as green manure crops for 56 days on grey forest degraded sandy loam soil, pH 6.5–7.0, were analysed. Aluminum content was determined using an inductively coupled plasma optical emission spectrometer (ICPOES) ICAP 6300 Duo. The possibility of metal accumulation in plant tissues was assessed using the bioconcentration factor (BF). Results. Measurements showed the following content of Al in plant tissues (in abs. dry matter): oilseed radish, variety ‘Kyianochka’ – 2035.9 mg/kg, white mustard, variety ‘Soniachna’ – 687.5 mg/kg, winter rapeseed, variety ‘Horlytsia’ – 388.6 mg/kg, Sarepta mustard, variety ‘Zolotava’ – 1238.5 mg/kg, winter turnip rape, variety ‘Oriana’ – 1105.2 mg/kg, tyfon, variety ‘Fitopal’ – 854.4 mg/kg. Conclusions. Under growing conditions, the aluminum content in plants did not exceed 0.2%. All the samples studied have a BF < 1 and are not hyperaccumulators of the element according to this criterion. However, three of the investigated samples (‘Zolotava’ Sarepta mustard, ‘Oriana’ winter turnip rape and ‘Kyianochka’ oilseed radish) have an aluminum content in the aboveground dry matter of more than 1000 mg/kg, indicating a significant accumulation of this element. For the purposes of phytoextraction of aluminum, the most suitable of the plants studied is oilseed radish ‘Kyianochka’ (BF ≈ 0.4). Мета. Встановити рівень накопичення алюмінію (Аl) у рослинах представників родини Brassicaceae, використовуваних як сидерати у сільському господарстві та перспективних для фіторемедіації ґрунтів. Предметом дослідження були такі культури, як редька олійна [cорт ‘Кияночка’ (Raphanus sativus L. var oleiformis Pars. ‘Kyianochka’)], гірчиця біла [сортозразок ‘Сонячна’ (Sinapis alba L. ‘Soniachna’)], ріпак озимий [сортозразок ‘Горлиця’ (Brassica napus L. ‘Horlytsia’)], гірчиця сарептська [сортозразок ‘Золотава’ (Brassica juncea (L.) Czern. ‘Zolotava’)], суріпиця озима [сорт ‘Оріана’ (Brassica campestris var. oleifera f. biennis D.C. ‘Oriana’)], тифон [сорт ‘Фітопал’ (Brassica campestris var. oleifera f. biennis DC. × Brassica rapa L. ‘Fitopal’)].  Методи. Дослідження проводили в Національному ботанічному саду імені М. М. Гришка НАН України (м. Київ). Рослини, що вирощували як сидерати, аналізували протягом 56 днів на сірому лісовому деградованому супіщаному малогумусному ґрунті, pH 6,5–7,0. Вміст алюмінію визначали, використовуючи оптичний емісійний спектрометр з індуктивно зв’язаною плазмою (ІCPОЕS) ІCAP 6300 Duo. Можливість накопичення металу в тканинах рослин оцінювали за допомогою біоконцентраційного фактора (ВF). Результати. Здійснивши вимірювання, встановили такий вміст Аl у тканинах рослин (у перерахунку на абсолютно суху речовину): редька олійна (сорт  ‘Кияночка’) – 2035,9 мг/кг; гірчиця біла (сортозразок ‘Сонячна’) – 687,5; ріпак озимий (сортозразок ‘Горлиця’) – 388,6; гірчиця сарептська (сортозразок ‘Золотава’) – 1238,5; суріпиця озима (сорт ‘Оріана’) – 1105,2; тифон (сорт ‘Фітопал’) – 854,4 мг/кг. Висновки. Вміст алюмінію в рослинах за наявних умов вирощування не перевищував 0,2%. Всі досліджені зразки мали показник BF < 1 та не були гіпернакопичувачами елемента за цим критерієм. Однак сортозразок гірчиці сарептської ‘Золотава’, сорт суріпиці озимої ‘Оріана’ та сорт редьки олійної ‘Кияночка’ продемонстрували значне накопичення алюмінію в наземній сухій масі – понад 1000 мг/кг. Найпридатнішою для фітоекстракції алюмінію серед досліджуваних рослин виявилася редька олійна ‘Кияночка’ (BF ≈ 0,4).